﻿Especificação e implementação de um protótipo de serviço web para buscas baseadas em contextos compartilhados definidos a partir de sintagmas e relacionamentos - Paiva, Fábio Augusto Procópio de (2006)
﻿The popularization of the Internet has stimulated the appearance of Search Engines that have as their objective aid the users in the Web information research process. However, it s common for users to make queries and receive results which do not satisfy their initial needs. The Information Retrieval in Context (IRiX) technique allows for the information related to a specific theme to be related to the initial user query, enabling, in this way, better results. This study presents a prototype of a search engine based on contexts built from linguistic gatherings and on relationships defined by the user. The context information can be shared with softwares and other tool users with the objective of promoting a socialization of contexts